Functional software size measurement methodology with effort estimation and performance indication - Singh, Jasveer, 1955- (Hoboken, New Jersey : Wiley : IEEE Press, 2017)
Presents a new, effective methodology in software size measurement Software size measurement is an extremely important and highly specialized aspect of the software life cycle. It is used for determining the effort and cost estimations for project planning purposes of a software project's execution, and/or for other costing, charging, and productivity analysis purposes. Many software projects exceed their allocated budget limits because the methodologies currently available lack accuracy. The new software size measurement methodology presented in this book offers a complete procedure that overcomes the deficiencies of the current methodologies, allowing businesses to estimate the size and required effort correctly for all their software projects developed in high-level languages. The Functional Software Size Measurement Methodology with Effort Estimation and Performance Indication (FSSM) allows for projects to be completed within the defined budget limits by obtaining accurate estimations. The methodology provides comprehensive and precise measurements of the complete software whereby factual software size determination, development effort estimation, and performance indications are obtained. The approach is elaborate, effective, and accurate for software size measurement and development effort estimation, avoiding inaccurate project planning of software projects. Key features: . Pinpoints one of the major, originating root causes of erroneous planning by disclosing hidden errors made in software size measurement, and consequently in effort estimates and project planning. All the major relevant and important aspects of software size measurement are taken into consideration and clearly presented to the reader Functional Software Size Measurement Methodology with Effort Estimation and Performance Indication is a vital reference for software professionals and Master level students in software engineering.
FSSM: Introduction. Introduction to Functional Software Size Measurement -- Synopsis of the Functional Software Size Measurement Methodology with Effort Estimation and Performance Indication (FSSM) -- FSSM: Software View. Software's Measurable Components in the FSSM -- Software Component's Measurable Features in the FSSM -- FSSM: Measurements. Software Component's Feature Points in the FSSM -- Software Component's Feature Point Counts in the FSSM -- Software Component's Measurements through Software Component's Feature Measurements in the FSSM -- FSSM: Estimations and Indications. Software Size Determination and Effort Estimations in the FSSM -- Software Performance Quality Indicators for Static Structure and Dynamic Characteristics in the FSSM -- FSSM: Summary Charts. Summary Charts of the FSSM -- FSSM: Strengths. Software Diagnostics Based on the Software Component's Feature Measurements and Software Performance Quality Indicators in the FSSM -- Convertibility and ISO/IEC Standards Compliance of the FSSM -- Significant Strengths of the FSSM -- FSSM: Usage -- Example. Example for Using the FSSM -- Concluding Information. Effort Estimate for the Usage of the FSSM -- Known Limitations, Improvement Scope, and Conclusion -- Glossary. Glossary -- List of Figures and Answers to Exercises. List of Figures -- Answers to Exercises.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Software measurement; Computer software -- Evaluation; Mesure du logiciel; Logiciels; COMPUTERS -- Software Development & Engineering -- General; Computer software -- Evaluation; Software measurement